Potential actions for preventing high consumption of Non-Nutritive Sweeteners among Chilean children and adolescents: recommendations from a panel of relevant actors - Marcela Reyes; Constanza Pino; Alejandra Ortega; Isabel Pemjean; Camila Corvalán; María Luisa Garmendia (Cambridge University Press, 2024)
Abstract Objective: To provide local policymakers with a guideline of potential actions to prevent the high consumption of Non-Nutritive Sweeteners (NNS) among children and adolescents observed in Chile, given the potential health problems related to NNS intake. Design: The Delphi method was used for the evaluation of twenty-one recommendations to decrease the intake of NNS in paediatric population, with the participation of a panel of relevant actors. Setting: The proposed recommendations were developed by the research team using the NOURISHING framework; potential actions were based on the increase in the use and intake of NNS by Chilean children, current local food regulations, recommendations of health organisations and foreign policy experiences. Participants: Twenty-five relevant actors related to NNS, nutrition, food technology and paediatrics (out of thirty-nine invitations made to scholars, professional institutions and civil society's organisations) participated in the Delphi study. Results: A consensus was reached on nine recommendations regarding relevance and feasibility to be part of the guideline. Recommendations involved measures mostly related to improving the delivery of information (food content and potential health effects of NNS), supporting the generation of more evidence of NNS health effects and substitutes, and marketing restrictions when targeted to children. Conclusions: The process produced a nine-action guideline to reduce the excessive NNS consumption among Chilean children and adolescents. Developed through a consensus-driven approach among key stakeholders, this guideline provides policymakers with a framework to adopt a precautionary stance, particularly concerning vulnerable populations, given the currently inconclusive evidence on the long-term health effects of NNS consumption.